Auditor Task Prioritization - Dierynck, Bart; Peters, Christian P. H. (Contemporary Accounting Research, 2026)
ABSTRACT We study how auditors prioritize tasks and how variations in task order influence auditors' performance. Drawing on conservation of resources theory, we develop and test our hypotheses through three experiments involving over 350 professional auditors. The first two experiments assess the impact of task order on performance. Across two settings, we manipulate task order and find that prioritizing an easier task generally results in lower performance compared with prioritizing a difficult task. In the third experiment, auditors are given autonomy over task ordering. We observe a tendency to prioritize easier tasks, particularly under heightened time pressure. We do not find any evidence that psychological ownership weakens the effect of time pressure on easy task prioritization.